Enhancing Hydrogen Production From The Pyrolysis Of Oil Palm EFB by Alkali Metal Oxides / Ramlan Zailani ... [et al.] - Zailani, Ramlan; Kamarudin, Khairul Ashraf; Raja Deris, Raja Razuan; Ismail, Khudzir (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The pyrolysis gas of oil palm empty fruit bunches (EFB) was investigated in a fixed bed reactor. The yields and distributions of the pyrolysis products were studied under various operating conditions. In the absence of any additive, the amount and composition of volatile released from EFB depended mainly on the pyrolysis temperature. The pyrolysis gas was analysed for the fractional species distribution. The total yields of hydrogen, Methane, CO and CO2 were obtained through the reaction at a temperature range of 300-600 oC. The total yield of hydrogen were dramatically improved to almost 100% with the addition of Sodium Hydroxide (NaOH) and Calcium Oxide (CaO). Hydrogen without CO and CO2 was produced through the reactions of EFB volatiles with NaOH and water to produce hydrogen, sodium carbonate (Na2CO3), and a small amount of methane as the by-product. The pyrolysis with inexpensive and abundant sorbent such as NaOH and CaO could produce hydrogen-rich gas which is free of CO and CO2, and the process could be optimized at relatively low temperature of 400-500 oC, which is significantly lower than the normal temperature ranges for biomass gasification to produce syngas fuel.